2010
DOI: 10.1007/s10840-010-9511-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of very high defibrillation thresholds (DFT) and efficacy of subcutaneous (SQ) array insertion during implantable cardioverter defibrillator (ICD) implantation

Abstract: Very high DFTs occur in about 5% of patients undergoing ICD implantation and may be predicted by LV dilation and amiodarone use. SQ array insertion reliably corrects this problem over other interventions with a low rate of procedural complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…Osswald et al [14] observed high defibrillation threshold in 6.3% of patients. Verma et al [15] defined high defibrillation threshold as an unsuccessful 25 J shock, observed that phenomenon in 5.1% of patients, and implanted subcutaneous leads in all such patients with final success. Brigniole et al [6] did not achieve a 10 J safety margin in 7% of patients in their group, and in 3.6% of patients even the shock with maximal output energy was not efficient.…”
Section: Discussionmentioning
confidence: 99%
“…Osswald et al [14] observed high defibrillation threshold in 6.3% of patients. Verma et al [15] defined high defibrillation threshold as an unsuccessful 25 J shock, observed that phenomenon in 5.1% of patients, and implanted subcutaneous leads in all such patients with final success. Brigniole et al [6] did not achieve a 10 J safety margin in 7% of patients in their group, and in 3.6% of patients even the shock with maximal output energy was not efficient.…”
Section: Discussionmentioning
confidence: 99%
“…A high DFT is a significant problem of ICD therapy, occurring in 3.9-12% of transvenous leads only systems depending on the patient populations [5][6][7]. Modern-day ICD pulse generators have many features specifically developed to combat the issue, including higher energy output, multiple programmable shock vectors, biphasic DF waveform as standard, and adjustable pulse widths of the two phases of the DF waveform in some models.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a strong desire to minimize the number of leads in the patient's body, as any such lead had a significant chance of failure during his natural lifespan [4] and being difficult to extract due to his vigorous fibrotic response to foreign bodies, insertion of one or more subcutaneous (SQ) array DF leads (model 6996SQ, Medtronic) in the left dorsolateral chest wall emerged as the favorite option [5]. As the patient had a low body mass index and there would be increased bulk in the device pocket with any SQ array leads, it was decided the pre-pectoral pocket should be converted into a sub-pectoral pocket at the same time.…”
Section: Case Historymentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25]27,28 System revisions may include moving the right ventricular coil, inactivating or activating the superior vena cava coil, adding an extra superior vena cava, azygous or subcutaneous 40 and certain drugs, such as amiodarone. 20,31,32,[41][42][43][44] However, the strengths of these associations are not consistent and vary between studies, with some studies demonstrating no good clinical correlates of high DFTs. 41,45 Because there is no way to reliably predict which patients will have a high DFT at implant, testing is still recommended.…”
Section: Discovery Of High Dfts Needing Systemmentioning
confidence: 99%